Aspect approach to determining the strategic position of an educational organization in the field of healthcare ("Journal "U". Economy. Management. Finance.", 2023)
The article discusses such an important area as preparing an organization for the development of a strategy, which goes through deep diagnostics, both of the external environment and the internal potential of the organization. Theoretical and methodological provisions for determining the strategic position of the organization on the basis of its deep diagnostics in the course of preparation for strategic planning are substantiated. The type of strategic behavior and the strategic position of the organization are determined, as a result of which certain management decisions are made.
Keywords: strategy; deep diagnostics; type of strategic behavior; strategic position; managerial decisions